Can music move people? : The effects of musical complexity and silence on waiting time - North, Adrian; Hargreaves, David (Sage Publications, Inc., 1999)
Previous research has suggested that music might influence the amount of time for which people are prepared to wait in a given environment. In an attempt to investigate the mechanisms underlying such effects, this study employed three levels of musical complexity and also a “no-music” condition. While one of these played in the background, participants were left to wait in a laboratory for the supposed start of an experiment. The results indicated that participants waited for the least amount of time during the no-music condition, and that there were no differences between the three music conditions. Other evidence indicated that this may be attributable to the music distracting participants’ attention from an internal timing mechanism. The results are discussed in terms of their implications for consumer behavior and research on the psychology of everyday life.